Diagnóstico sectorial de la actividad venta al por mayor de artículos de ferreterías del cantón Loja - Villa Cueva, Johanna Alexandra (2023)
The sectoral diagnosis allows the qualitative and quantitative characterization of a sector and can be done through multiple tools, one of which is by establishing indicators and metrics used to analyze and evaluate the performance of a sector. The objective of the research was to carry out a sectoral diagnosis of the wholesale activity of hardware stores in Loja canton, which allows knowing in what conditions the sector is. In order to fulfill this purpose, structured surveys were applied to 20 managers of companies operating in the ISIC G4663.21 activity. For the tabulation and establishment of industry statistics and averages, the winsorizing technique was applied to reduce the influence of outliers. The research found that hardware companies can evaluate their organizational performance by establishing financial and non- financial indicators designed to identify their critical success factors (assortment of merchandise, reliable suppliers, strategic location, etc.). Finally, the results allowed the conclusion that the hardware industry, at the level of financial indicators, has good liquidity of $ 3,68; it manages a working capital of $ 16 500 monthly, allowing it to cover the payment of suppliers, employees, essential services and to solve any unforeseen event; the level of indebtedness is low at 22%, and the profitability of the business is good, above 15%. Regarding non-financial indicators, the hardware industry has 69 % of its personnel under contract, generating income from sales, and daily productivity per employee is $ 423,00. Therefore, it is an attractive sector, generating profits and growth potential.